AC Pulsed Field Ablation Is Feasible and Safe in Atrial and Ventricular Settings: A Proof-of-Concept Chronic Animal Study - Caluori, Guido; Odehnalova, Eva; Jadczyk, Tomasz; Pesl, Martin; Pavlova, Iveta; Valikova, Lucia; Holzinger, Steffen; Novotna, Veronika; Rotrekl, Vladimir; Hampl, Ales; Crha, Michal; Cervinka, Dalibor; et al. (Frontiers in bioengineering and biotechnology, 2020)
INTRODUCTION: Pulsed field ablation (PFA) exploits the delivery of short high-voltage shocks to induce cells death via irreversible electroporation. The therapy offers a potential paradigm shift for catheter ablation of cardiac arrhythmia. We designed an AC-burst generator and therapeutic strategy, based on the existing knowledge between efficacy and safety among different pulses. We performed a proof-of-concept chronic animal trial to test the feasibility and safety of our method and technology. METHODS: We employed 6 female swine - weight 53.75 ± 4.77 kg - in this study. With fluoroscopic and electroanatomical mapping assistance, we performed ECG-gated AC-PFA in the following settings: in the left atrium with a decapolar loop catheter with electrodes connected in bipolar fashion; across the interventricular septum applying energy between the distal electrodes of two tip catheters. After procedure and 4-week follow-up, the animals were euthanized, and the hearts were inspected for tissue changes and characterized. We perform finite element method simulation of our AC-PFA scenarios to corroborate our method and better interpret our findings. RESULTS: We applied square, 50% duty cycle, AC bursts of 100 μs duration, 100 kHz internal frequency, 900 V for 60 pulses in the atrium and 1500 V for 120 pulses in the septum. The inter-burst interval was determined by the native heart rhythm - 69 ± 9 bpm. Acute changes in the atrial and ventricular electrograms were immediately visible at the sites of AC-PFA - signals were elongated and reduced in amplitude (p < 0.0001) and tissue impedance dropped (p = 0.011). No adverse event (e.g., esophageal temperature rises or gas bubble streams) was observed - while twitching was avoided by addition of electrosurgical return electrodes. The implemented numerical simulations confirmed the non-thermal nature of our AC-PFA and provided specific information on the estimated treated area and need of pulse trains. The postmortem chest inspection showed no peripheral damage, but epicardial and endocardial discolorations at sites of ablation. T1-weighted scans revealed specific tissue changes in atria and ventricles, confirmed to be fibrotic scars via trichrome staining. We found isolated, transmural and continuous scars. A surviving cardiomyocyte core was visible in basal ventricular lesions. CONCLUSION: We proved that our method and technology of AC-PFA is feasible and safe for atrial and ventricular myocardial ablation, supporting their systematic investigation into effectiveness evaluation for the treatment of cardiac arrhythmia. Further optimization, with energy titration or longer follow-up, is required for a robust atrial and ventricular AC-PFA.
Keywords: preclinical cardiology; irreversible electroporation (IRE); ventricular arrhythmia (VA); radiofrequency ablation; atrial fibrillation; pulsed field ablation